Inter-limb asymmetries and kicking limb preference in English premier league soccer players - Nicholson, Gareth; Bennett, Tim; Thomas, Aaron; Pollitt, Lysander; Hopkinson, Mike; Crespo, Rubén; Robinson, Tom; Price, Rob J. (Frontiers in Sports and Active Living, 2022)
The aims of this study were: (1) to quantify interlimb asymmetries in EPL soccer players in the context of kicking limb preference and (2) to establish the relationship between interlimb asymmetries and measures of physical performance. Twenty-two players (age: 21.8 ± 4.4 years) from an EPL club performed a running gait assessment (20 km/h) and unilateral countermovement jumps, a CoD assessment (modified 505 test), and an isokinetic knee extension/flexion protocol using each leg. Asymmetries were quantified using the percentage difference method and Pearson’s correlations were used to quantify the association between variables. Players displayed the greatest level of asymmetry in isokinetic strength measures (5.9-12.7%) and lower levels of asymmetry in gait (1.6-7.7%), jump (0.9-7.0%) and CoD (1.9-3.5%) assessments. The influence of the preferred kicking limb was most evident in the isokinetic assessment with the players showing dominance in the preferred limb for knee flexor strength and in the non-preferred limb for knee extensor strength. These manifested in the asymmetry values calculated for the hamstring:quadricep (H:Q) ratios at 60°/s (8.80 ± 7.82%) and 240°/s (11.22 ± 7.04%) and in the functional H:Q ratio (12.67 ± 8.25%). The asymmetry values for peak extensor moment at 240°/s showed a significant correlation (ρ = ─0.55, p = 0.034) with 10 m time in the CoD assessment. These findings provide benchmark asymmetry data for soccer practitioners and reveal that kicking limb preferences may bring about interlimb differences in the H:Q ratio which raises important considerations in the design of testing batteries and injury reduction interventions.